The relationship between propulsive force in tethered swimming and 200-m front crawl performance - Santos, K. B.; Bento, P. C. B.; Pereira, G.; Rodacki, A. L. F. (The Journal of Strength and Conditioning Research, 2016)
The aims of this study were to determine whether propulsive force (peak force, mean force, impulse, and rate of force development) and stroke rate change during 2 minutes of front crawl tethered swimming and to correlate them with the stroke rate and swimming velocity in 200-m front crawl swimming. Twenty-one swimmers (21.6 ± 4.8 years, 1.78 ± 0.06 m, 71.7 ± 8.1 kg), with 200-m front crawl swimming performance equivalent to 78% of the world record (140.4 ± 10.1 seconds), were assessed during 2 minutes of maximal front crawl tethered swimming (propulsive forces and stroke rate) and 200-m front crawl swimming (stroke rate and clean velocity). Propulsive forces decreased between the beginning and the middle instants (~20%; p = 0.05) but remained stable between the middle and the end instants (~6%; p > 0.05). The peak force was positively correlated with the clean velocity in the 200-m front crawl swimming (mean r = 0.61; p < 0.02). The stroke rates of the tethered swimming and 200-m front crawl swimming were positively correlated (r = 45; p= 0.01) at the middle instant. Therefore, the propulsive force and stroke rate changed throughout the 2 minutes of tethered swimming, and the peak force is the best propulsive force variable tested that correlated with 200-m front crawl swimming performance.